The study of droplet deformation and droplet volume fraction in an aero-engine bearing chamber. (May 2019) - Fang, Long; Chen, Guoding
Inside an aero-engine bearing chamber, the shape, velocity, and temperature of each droplet shed from roller elements keep changing under the actions of the rotating airflow. Research on droplet deformation, droplet motion, and droplet volume fraction is fundamental to the understanding of the complex two-phase flow in an aero-engine bearing chamber. In this paper, the modified Taylor analogy breakup model, equations of temperature and motion are established to obtain the size, temperature, and velocity of a deformed droplet. Subsequently, a method is presented to solve for the droplet volume fraction in a bearing chamber based on the size and motion parameters of deformed droplets. In the end, a simplified bearing chamber experimental setup has been constructed. Comparisons between the experimental results and theoretical calculations show a good match based upon the research analogy used. The research work in this paper can provide theoretical foundations for the analyses of heat exchange and lubrication in bearing chambers. This also has great significance in realizing the rigorous design required for the lubrication system of an aero-engine.